Implementation of Free Text Format Nursing Diagnoses at a University Hospital's Medical Department. Exploring Nurses' and Nursing Students' Experiences on Use and Usefulness. A Qualitative Study. (13th May 2015) - Frigstad, Sigrun Aasen; Nøst, Torunn Hatlen; André, Beate
Abstract : Background . Nursing documentation has long traditions and represents core element of nursing, but the documentation is often criticized of being incomplete. Nursing diagnoses are an important research topic in nursing in terms of quality of nursing assessment, interventions, and outcome in addition to facilitating communication and continuity. Aim . The aim of this study was to explore the nurses' and nursing students' experiences after implementing free text format nursing diagnoses in a medical department. Method . The study design included educational intervention of free text nursing diagnoses. Data was collected through five focus group interviews with 18 nurses and 6 students as informants. The data was analyzed using qualitative content analysis. Results . The informants describe positive experiences concerning free text format nursing diagnoses' use and usefulness; it promotes reflection and discussion and is described as a useful tool in the diagnostic process, though it was challenging to find the diagnosis' appropriate formulation. Conclusion . Our findings indicate a valid usability of free text format nursing diagnoses as it promotes the diagnostic process. The use seems to enhance critical thinking and may serve as valuable preparation towards an implementation of standardized nursing diagnoses. Use and support of key personnel seem valuable in an implementation process.